Revealing macrozoobenthos diversity of Java coral reefs, Indonesia: a review on research trends and species assemblages - Aulia, Elsa Dianita; Park, Jinsoon; Lee, Sang-kyu; Khim, Jong Seong (Frontiers in Marine Science, 2024)
Macrozoobenthos communities play significant ecological roles in coral reef ecosystems. However, they are frequently overlooked due to their cryptic appearance, and their diversity remains undiscovered, particularly in Indonesia. This comprehensive review of publications on the macrozoobenthos in the coral reef ecosystems of Java - the most populated island in Indonesia, was conducted to compile a species list and gain an overview of its community composition. We also assessed the existence of species that are frequently reported, endemic, protected, and threatened. Data analysis was performed with data from 53 publications appearing from the 1980s to 2022. In total, 482 species belonging to 4 phyla and 9 classes have been recorded. Mollusca is the most speciose phylum (n = 321), followed by Echinodermata (n = 106), Arthropoda (n = 49), and Platyhelminthes (n = 6). Generally, the northern part of Java is well studied and has larger numbers of recorded phyla and species. The highest species number (n = 266) has been recorded off the northern coast of West Java, while there are around 25–99 species in other regions. Echinoderms species such as Culcita novaeguineae, Diadema setosum, Echinothrix calamaris, and Holothuria atra had relatively higher occurrences than other taxa. We also noted the occurrence of giant clam Hippopus hippopus, which is protected by Indonesian law. This review provides fundamental knowledge of macrozoobenthic diversity in the coral reefs of Java, making it available to global audiences. However, it revealed a lack of research on benthic fauna in several areas with moderate to good coral cover conditions. Further research is needed to explore macrozoobenthic species richness in this region thoroughly, and periodic monitoring is essential to provide early warnings of possible changes and biodiversity loss.